Aflatoxin B1: Mechanism of mutagenesis - Santella, Regina M. (Iatreia, 2007)
Aflatoxins are a group of toxic and carcinogenic fungal metabolites that frequently contaminate corn, peanuts and other products. Aflatoxin B1 (AFB1), the most potent of these, is metabolized by the cytochrome P450 system into a number of hydroxylated metabolites and glutathione conjugates in the process of conversion to more hydrophilic forms for urinary excretion. Unfortunately, one of these metabolites is the aflatoxin-8,9-epoxide that is produced in two forms, endo and exo. Glutathione S-transferases (GST) are able to conjugate and detoxify this reactive intermediate. Species differences in susceptibility to the effects of AFB1 are partially related to differences in expression of specific GSTs that are able to conjugate the epoxide to glutathione. The exo epoxide is able to intercalate into DNA and this is followed by reaction of the C8 position of the epoxide with the N7 position of guanine. NMR studies of oligonucleotide duplexes containing the adduct have demonstrated that the adduct exists with the aromatic portion intercalated on the 5' face of the guanine residue with Watson-Crick base pairing maintained. However, this covalent adduct is chemically unstable due to the charge on the ribose ring. As a result, the guanine can be released from the DNA leaving an apurinic site. This released guanine adduct can be detected in the urine and serves as a biomarker of exposure to AFB1. Alternatively, the ribose ring opens forming a stable formamidopyrimidine (FAPY) adduct. This adduct somewhat stabilizes the DNA duplex. Time course studies in animals have demonstrated that the N7 adduct is rapidly removed, probably because it causes more distortion in the helix, while the FAPY adduct is more persistent. The FAPY adduct has been detected in rat liver weeks after exposure. In addition, oxidative metabolism of AFB1 results in oxidative stress and increased levels of oxidative DNA damage including 8-oxodeoxyguanosine are found in cells treated with AFB1. All these types of DNA damage are mutagenic primarily resulting in G to T transversions but G to A or G to C mutations are also observed at a lower frequency. Mutations adjacent to the site of adduct formation can also occur probably due to the bulkiness of AFB1 adducts. Studies in animals have demonstrated a linear dose-response between AFB1-DNA adducts and liver tumors. Studies in bacteria have demonstrated that the FAPY adduct is more mutagenic than AFB1- Gua. In bacteria, the FAPY adducts is the strongest block to replication even in the presence of bypass polymerases and thus a prime candidate for the extreme toxicity of AFB. The nucleotide excision repair pathway is the major pathway responsible for removal of bulky AFB1 adducts while base excision repair removes oxidative DNA damage and apurinic sites. Thus, in vivo differences in activities in these repair pathway will impact on HCC risk. AFB1 exposure is also associated with a specific codon 249 AGG (arginine) to AGT (serine) mutation in the p53 tumor suppressor gene that inactivates the protein. This mutation is specifically found in HCC from regions with high AFB1 exposure and not from regions with low AFB1 exposure.